The Effect of a Combination Treatment Using Palonosetron, Promethazine, and Dexamethasone on the Prophylaxis of Postoperative Nausea and Vomiting and QTc Interval Duration in Patients Undergoing Craniotomy under General Anesthesia: A Pilot Study - Bergese, Sergio D.; Puente, Erika G.; Antor, Maria A.; Capo, Gerardo; Yildiz, Vedat O.; Uribe, Alberto A. (Frontiers in Medicine, 2016)
Introduction: Postoperative nausea and vomiting (PONV) is a displeasing experience that distresses surgical patients during the first 24 hours after a surgical procedure. The incidence of postoperative nausea occurs in about 50%, the incidence of postoperative vomiting is about 30%, and in high-risk patients, the PONV rate could be as high as 80%. Therefore, the study design of this single arm, non-randomized, pilot study assessed the efficacy and safety profile of a triple therapy combination with palonosetron, dexamethasone and promethazine to prevent PONV in patients undergoing craniotomies under general anesthesia. Methods: The research protocol was approved by the institutional review board and 40 subjects were provided written informed. At induction of anesthesia, a triple therapy of palonosetron 0.075 mg IV, dexamethasone 10 mg IV and promethazine 25 mg IV was given as PONV prophylaxis. After surgery, subjects were transferred to the surgical intensive care unit (SICU) or post anesthesia care unit as clinically indicated. Ondansetron 4 mg IV was administered as primary rescue medication to subjects with PONV symptoms. PONV was assessed and collected every 24 hours for 5 days via direct interview and/or medical charts review. Results: The overall incidence of PONV during the first 24 hours after surgery was 30% (n=12). The incidence of nausea and emesis 24 hours after surgery was 30% (n=12) and 7.5% (n=3) respectively. The mean time to first emetic episode, first rescue, and first significant nausea was 31.3 (±33.6) 15.1 (±25.8) and 21.1 (±25.4) hours, respectively . The overall incidence of nausea and vomiting after 24-120 hours period after surgery was 30% (n=12). The percentage of subjects without emesis episodes over 24-120 h postoperatively was 70% (n=28). No subjects presented a prolonged QTC interval ≥500 msec before and/or after surgery. Conclusion: Our data demonstrated that this triple therapy regimen may be an adequate alternative regimen for the treatment of postoperative nausea and vomiting in patients undergoing neurological surgery under general anesthesia. More studies with a control group should be performed to demonstrate the efficacy of this regimen and that palonosetron is a low risk for QTc prolongation.